Superior explicit memory despite severe developmental amnesia: In‐depth case study and neural correlates. Issue 12 (6th November 2018) - Jonin, Pierre‐Yves; Besson, Gabriel; La Joie, Renaud; Pariente, Jérémie; Belliard, Serge; Barillot, Christian; Barbeau, Emmanuel J.
Abstract: The acquisition of new semantic memories is sometimes preserved in patients with hippocampal amnesia. Robust evidence for this comes from case reports of developmental amnesia suggesting that low‐to‐normal levels of semantic knowledge can be achieved despite compromised episodic learning. However, it is unclear whether this relative preservation of semantic memory results from normal acquisition and retrieval or from residual episodic memory, combined with effortful repetition. Furthermore, lesion studies have mainly focused on the hippocampus itself, and have seldom reported the state of structures in the extended hippocampal system. Preserved components of this system may therefore mediate residual episodic abilities, contributing to the apparent semantic preservation. We report an in‐depth study of Patient KA, a 27‐year‐old man who had severe hypoxia at birth, in which we carefully explored his residual episodic learning abilities. We used novel speeded recognition paradigms to assess whether KA could explicitly acquire and retrieve new context‐free memories. Despite a pattern of very severe amnesia, with a 44‐point discrepancy between his intelligence and memory quotients, KA exhibited normal‐to‐superior levels of knowledge, even under strict time constraints. He also exhibited normal‐to‐superior recognition memory for new material, again under strict time constraints. Multimodal neuroimaging revealed an unusual pattern of selective atrophy within each component of the extended hippocampal system, contrasting with the preservation of anterior subhippocampal cortices. A cortical thickness analysis yielded a pattern of thinner but also thicker regional cortices, pointing toward specific temporal lobe reorganization following early injury. We thus report the first case of superior explicit learning and memory in a severe case of amnesia, raising important questions about how such knowledge can be acquired.